Implementasi Kebijakan Administrasi Desa dalam Pelayanan Publik diKecamatan Amurang Timur Kabupaten Minahasa Selatan - Mangimpis, Adelfia Crestofiane; Rumapea, Patar; Lalom, Alden (Sam Ratulangi University, 2014)
Abstract : The vast of the territory of Indonesia to be one reason for the administrative arrangements were observed from the smallest region or the so-called village. To improve the management of village government needs to restructure the administration as Permendagri No. 32 of 2006 on Guidelines for the Village Administration to be more effective and efficient. The purpose of this research is to describe, analyze and know how the village administration policy implementation in public service as well as any constraints in the implementation of policies in the village administration of public services in the District of East Amurang South Minahasa. This study used qualitative methods of data analysis are presented descriptively with random village sampling technique or random sampling of eight villages that were taken three villages in the district of East Amurang South Minahasa and the number of informants is sixteen informants. From the results of existing research, the implementation of the existing village administration has not been completely worked well because of the resources and infrastructure that supports the public service yet,Â but with the shortage of all parties work together to seek the implementation of village administration effective and efficient. Keywords : Policy Implementation, Rural Administration, Public Service.